PSIX-33 Student perceptions on the ability of a certificate in equine science to prepare them for obtaining an industry career. (7th December 2018) - Martinez, R; Leatherwood, J; Walker, N; Much, M; Vogelsang, M
Abstract: Texas A&M University offers undergraduate students the opportunity to pursue a Certificate in Equine Science. The required courses, taken in sequence, are designed to prepare graduates for qualified positions within the equine industry. The objective of this survey was to evaluate student perception on the ability of certificate courses to appropriately prepare them for obtaining a career in the equine industry. Students (n=82) enrolled in four senior level courses were asked to complete an online survey. Eighty-two student (5 males and 77 females; 19 to 33 yr) responses from those pursuing an equine certificate, were collected using an online data collection software (Qualtrics, Provo, UT). Students (71.95%) implied that they planned on pursuing a career within the equine industry following their collegiate education with 43.90% planning on attending graduate or veterinary school upon graduation, 31.71% undecided and 24.39% of students did not plan on attending graduate or veterinary school. Students also suggested that they had an increased awareness of potential employment opportunities within the equine industry after enrolling in the equine careers and industry preparation course with 29.27% strongly agreeing, 42.68% agreeing, 14.63% somewhat agreeing. When asked which segment of the industry the equine courses best prepared them for, students responded production and management (51.22%), nutrition and health (20.73%), marketing and sales (12.20%), behavior and training (9.76%) and veterinary medicine (6.10%). The survey results indicate that 34.15% of students find a career in veterinary medicine most appealing, followed by 23.17% in business and management. These data suggest that the equine sector is very appealing as a future career course for graduates. Gaining a better understanding of student perceptions may assist faculty in identifying potential curriculum alterations that may better prepare future students that are interested in obtaining the equine certificate.